2020
DOI: 10.1124/dmd.120.090704
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infection and Inflammation on Drug Metabolism, Active Transport, and Systemic Drug Concentrations in Veterinary Species

Abstract: Within human medicine, it is recognized that the pharmacokinetics (PK) of many compounds can be altered by the presence of inflammation or infection. Research into the reason for these changes has identified pathways that can influence drug absorption, clearance, and tissue distribution. In contrast, far less is known about these relationships within the framework of veterinary medicine. Rather, most of the PK data generated in veterinary species employs healthy subjects, raising the question of whether these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Thus, the observed overall agreement between the in vitro and in vivo metabolic clearances in response to inflammation reflected the contribution of the hepatic metabolizing enzyme. A significant amount of evidence has been reported on the relationships between inflammation on drug-metabolizing enzyme activity [ 13 , 21 , 35 ]. However, discrepancies still exist in available investigations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the observed overall agreement between the in vitro and in vivo metabolic clearances in response to inflammation reflected the contribution of the hepatic metabolizing enzyme. A significant amount of evidence has been reported on the relationships between inflammation on drug-metabolizing enzyme activity [ 13 , 21 , 35 ]. However, discrepancies still exist in available investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, discrepancies still exist in available investigations. Martinez et al [ 21 ] suggested that some of the apparent dissimilarities may be attributed to animal species and the duration of exposure to these cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms for a decrease in volume of distribution, which would result in decreased clearance in the MKPV-infected B6 group, would include dehydration or increased drug protein binding. Both of these conditions may occur in disease, but in particular the latter may occur in a pro-inflammatory state associated with systemic infection 37 . MKPV-infected NSG mice had lower C0 than uninfected mice, suggesting a higher volume of distribution.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges is the proportionally small amount of information on canine enzymes and transporters as compared to that in humans. Furthermore, a major drawback is the frequent reliance on mRNA for identification of location and changes in transporters and drug-metabolizing enzymes (159). It is difficult to compare human and canine enzyme and transporter activity on the basis of anything other than expressed activities.…”
Section: Concluding Commentsmentioning
confidence: 99%